Penanganan Narapidana Teroris Di Lembaga Pemasyarakatan Indonesia - Runturambi, Arthur Josias Simon (UI Scholars Hub, 2018)
This paper describes the handling of terrorist prisoners in prisons in Indonesia in order to find a model of handling that not only concerns the security aspect (security) but also the prosperity aspect in the process of fostering the perpetrators of terrorism and in order to reduce radicalism. The analysis in this paper shows that each prison has a different problem so that different handling strategies are performed, although there is still the same handling pattern.